2011
DOI: 10.1198/jasa.2011.tm10370
|View full text |Cite
|
Sign up to set email alerts
|

Robust, Adaptive Functional Regression in Functional Mixed Model Framework

Abstract: Functional data are increasingly encountered in scientific studies, and their high dimensionality and complexity lead to many analytical challenges. Various methods for functional data analysis have been developed, including functional response regression methods that involve regression of a functional response on univariate/multivariate predictors with nonparametrically represented functional coefficients. In existing methods, however, the functional regression can be sensitive to outlying curves and outlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 46 publications
1
75
0
1
Order By: Relevance
“…Note that both Gfmm and Rfmm are not methodologically new. The general methods have been proposed by Morris and Carroll (2006) and Zhu et al (2011); extensions and applications can be found in Zhu et al (2012), Martinez et al (2013), Lee and Morris (2016), among others. The purpose of this section is not to propose a brand new model, but to outline the FMMs in the context of sonar-terrain data analysis, with the goal of integrating them in the unified analytical framework in Section 4.…”
Section: The Functional Mixed Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that both Gfmm and Rfmm are not methodologically new. The general methods have been proposed by Morris and Carroll (2006) and Zhu et al (2011); extensions and applications can be found in Zhu et al (2012), Martinez et al (2013), Lee and Morris (2016), among others. The purpose of this section is not to propose a brand new model, but to outline the FMMs in the context of sonar-terrain data analysis, with the goal of integrating them in the unified analytical framework in Section 4.…”
Section: The Functional Mixed Modelsmentioning
confidence: 99%
“…The prior for Blk is set similarly with the prior for Galk. These formulations are equivalent to setting double exponential (DE) distributions for the residuals, the random effects, and the “slab” part of the fixed effects, which has the effect of accommodating heavier-tailed behavior (non-Gaussianity) in data and downweighting the effect of outlying curves or outlying regions (Zhu et al, 2011). …”
Section: The Functional Mixed Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many parametric mixed effects models including both fixed and random effects are the predominant approach for characterizing both the temporal correlations and random individual variations. Although there is a great interest in the analysis of functional data with various levels of hierarchical structures [11, 18, 7], only a handful of them [6, 17, 21] focused on the development of linear mixed models for longitudinal image data. Recently, there was some attempt on the development of hierarchical geodesic models on diffeomorphism for longitudinal shape analysis [15].…”
Section: Introductionmentioning
confidence: 99%